A framework to assess solar PV irrigation system (SPIS) for sustainable rice farming in Sorsogon, Philippines - Escoto, Bryan Encinas; Abundo, Michael Lochinvar (International Journal of Renewable Energy Development, 2024)
Solar PV irrigation system (SPIS) has proven its potential to impact the agricultural sector. It is known for producing zero GHG emissions, and recent studies have proved its effectiveness compared to fuel-based pumps. However, some factors affecting its operations and economic viability that require further study. This study assessed the viability and sustainability of SPIS for providing rice irrigation in the province of Sorsogon, Philippines. Our objectives were to a) identify the optimal deployment locations, b) determine the most effective energy system configurations for rice irrigation, and c) assess the impact on achieving SDGs. Analysis showed that 17% of the province's total land area is suitable for SPIS deployment. A one-hectare land requires 3.302 kWh of energy per day and a water pump with a peak power of 1.1 kW. The optimal energy configuration provided an annual energy of 8,547 kWh from the Solar PV system and an additional 119 kWh delivered by the diesel generator. This setup demonstrates the lowest net present cost (NPC) of ₱ 1,079,642 and the lowest levelized cost of electricity (LCOE) of ₱ 17.79/kWh. A future SPIS project was assessed to have 27 possible synergies and 3 tradeoffs that impact achieving sustainable development goals (SDGs). The participation of stakeholders, along with local farmers, in discussions about adapting SPIS projects will help ensure the sustainability of the application and the acceptance of the technology. The findings of this study introduced new insights and understanding of the critical aspects of solar PV irrigation system applications.